Mitochondrial dysfunction in skeletal muscle contributes to the development of acute insulin resistance in mice. Issue 6 (3rd October 2021) - Lee, Hyunjung; Ha, Tae Youl; Jung, Chang Hwa; Nirmala, Farida Sukma; Park, So‐Young; Huh, Yang Hoon; Ahn, Jiyun
Abstract: Background: Although mounting evidence indicates that insulin resistance (IR) co‐occurs with mitochondrial dysfunction in skeletal muscle, there is no clear causal link between mitochondrial dysfunction and IR pathogenesis. In this study, the exact role of mitochondria in IR development was determined. Methods: Six‐week‐old C57BL/6 mice were fed a high‐fat diet for 2 weeks to induce acute IR or for 24 weeks to induce chronic IR ( n = 8 per group). To characterize mitochondrial function, we measured citrate synthase activity, ATP content, mitochondrial DNA (mtDNA) content, and oxygen consumption rate in gastrocnemius and liver tissues. We intraperitoneally administered mitochondrial division inhibitor 1 (mdivi‐1) to mice with acute IR and measured mitochondrial adaptive responses such as mitophagy, mitochondrial unfolded protein response (UPRmt), and oxidative stress ( n = 6 per group). Results: Acute IR occurred coincidently with impaired mitochondrial function, including reduced citrate synthase activity (−37.8%, P < 0.01), ATP production (−88.0%, P < 0.01), mtDNA (−53.1%, P < 0.01), and mitochondrial respiration (−52.2% for maximal respiration, P < 0.05) in skeletal muscle but not in liver. Administration of mdivi‐1 attenuated IR development by increasing mitochondrial function (+58.5% for mtDNA content, P < 0.01; 4.06 ± 0.69 to 5.84 ± 0.95 pmol/min/mg for citrate synthase activity, P < 0.05; 13.06 ± 0.70 to 34.87 ± 0.70 pmol/min/g for maximal respiration, P < 0.001). Western blot analysis showed acute IR resulted in increased autophagy (mitophagy) and UPRmt induction in muscle tissue. This adaptive response was inhibited by mdivi‐1, which reduced the mitochondrial oxidative stress of skeletal muscle during acute IR. Conclusions: Acute IR induced mitochondrial oxidative stress that impaired mitochondrial function in skeletal muscle. Improving mitochondrial function has important potential for treating acute IR.